LncRsp1, a long noncoding RNA, influences Fgsp1 expression and sexual reproduction in Fusarium graminearum. (29th November 2021) - Wang, Jie; Zeng, Wenping; Cheng, Jiasen; Xie, Jiatao; Fu, Yanping; Jiang, Daohong; Lin, Yang
Abstract: Long noncoding RNAs (lncRNAs) are crucial regulators of gene expression in many biological processes, but their biological functions remain largely unknown, especially in fungi. Fusarium graminearum is an important pathogen that causes the destructive disease Fusarium head blight (FHB) or head scab disease on wheat and barley. In our previous RNA sequencing (RNA‐Seq) study, we discovered that lncRsp1 is an lncRNA that is located +99 bp upstream of a putative sugar transporter gene, Fgsp1, with the same transcription direction. Functional studies revealed that Δ lncRsp1 and Δ Fgsp1 were normal in growth and conidiation but had defects in ascospore discharge and virulence on wheat coleoptiles. Moreover, lncRsp1 and Fgsp1 were shown to negatively regulate the expression of several deoxynivalenol (DON) biosynthesis genes, TRI4, TRI5, TRI6, and TRI13, as well as DON production. Further analysis showed that the overexpression of lncRsp1 enhanced the ability of ascospore release and increased the mRNA expression level of the Fgsp1 gene, while lncRsp1 ‐silenced strains reduced ascospore discharge and inhibited Fgsp1 expression during the sexual reproduction stage. In addition, the lncRsp1 complementary strains lncRsp1‐LC‐1 and lncRsp1‐LC‐2 restored ascospore discharge to the level of the wild‐type strain PH‐1. Taken together, our results reveal the distinct and specific functions of lncRsp1 and Fgsp1 in F. graminearum and principally demonstrate that lncRsp1 can affect the release of ascospores by regulating the expression of Fgsp1 . Abstract : lncRsp1, a long noncoding RNA located +99 bp upstream of a putative sugar transporter gene Fgsp1, can affect the release of ascospores by regulating the expression of Fgsp1 in Fusarium graminearum .